Boosting Photothermal Theranostics via TICT and Molecular Motions for Photohyperthermia Therapy of Muscle‐Invasive Bladder Cancer. Issue 24 (8th September 2021) - Zeng, Sheng; Gao, Heqi; Li, Chuang; Xing, Shaoqiang; Xu, Zhaoliang; Liu, Qian; Feng, Guangxue; Ding, Dan
Abstract: The development of photothermal agents with high photothermal conversion efficiency (PCE) can help to reduce drug and laser dosage, but still remains a big challenge. Herein, a novel approach is reported to design photothermal agents with high PCE values by promoting nonradiative heat generation processes through the cooperation of twisted intramolecular charge transfer (TICT) and molecular motions. Within the designed molecule 2DMTT‐BBTD, the tetraphenylethenes act as molecular rotors, the long alkyl chain grafted thiophene helps to twist the molecular geometry to facilitate TICT state formation and preserve molecular motions in aggregate, while the strong electron‐withdrawing BBTD unit enhances TICT effect. 2DMTT‐BBTD exhibits NIR‐absorption and a high PCE value of 74.8% under 808 nm laser irradiation. Gambogic acid (GA) which surmounts tumor cell thermotolerance by inhibiting heat shock protein 90 (HSP90) expression is coloaded into the nanoparticles, RGD peptide is further introduced to the nanoparticle surface to improve tumor accumulation. The resultant nanoparticles facilitate the effective low‐temperature hyperthermia therapy of muscle‐invasive bladder cancer (MIBC) with minimal damage to surrounding heathy tissues. This work delivers a new design concept for development of highly efficient photothermal agents, which also provides a safer approach for noninvasive treatment of MIBC and other malignant tumors. Abstract : A photothermal agent 2DMTT‐BBTD is designed to boost photothermal conversion efficiency through cooperation of twisted intramolecular charge transfer and molecular motions, which shows a high value of 74.8% under 808 nm laser irradiation. With coloading of gambogic acid as a heat shock protein 90 inhibitor to reduce tumor cell thermoresistance, the resultant nanoparticles show effective photohyperthermia therapy of muscle‐invasive bladder cancer.